Åtal för brott mot djurskyddslagen och för djurplågeri : en analys av åtalsanmälningar, väckta åtal och fällande domar i sex län år 2013 - Eng, Hanna (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
There’s been an increasing interest in animal welfare the past few decades and right now the awareness of the importance to protect the animals in all types of food productions is very high in the European Union. In Sweden 13 700 controls of animal welfare were done in 2013. When the Swedish animal welfare legislation is broken by an animal keeper the animal welfare inspectors of the county of administrative boards reports that to the prosecutor or police in form of a notification of prosecution. The inspectors are writing these notifications because they want the animal keeper to be investigated and to be prosecuted in court. 336 notifications of prosecution were written during 2013 where the suspected crimes involved violations of the Swedish animal welfare legislation and animal cruelty. The aim of this study was to analyze the notifications of prosecution against violation of the Swedish animal welfare legislation and against animal cruelty, written by the animal welfare inspectors working in six different county administrative boards in the year 2013. The purpose was to see the progress of the notifications of prosecution to a possible prosecution in court and conviction. The counties involved were Jönköping, Kalmar, Stockholm, Södermanland, Uppsala and Västra Götaland. There were 125 notifications of prosecution to sort and analyze. 44 cases (35,2 %) were prosecuted in court and the result precipitated in 66 convictions. The three main reasons for the animal welfare inspectors to write a notification of prosecution were lack of veterinary care, lack of supervision of their animals and feed-related crimes. Of the 44 notifications prosecuted in court, Jönköping had the largest proportion of prosecutions with 55,6 %. The one county with the smallest proportion was Stockholm, with only 9,1 % of the notifications of prosecution that led to a prosecution. 61 notifications of prosecutions (48,8 %) led to at least one conviction. The counties with the largest proportion of a notification with at least one conviction were Södermanland and Jönköping with 66,7 % each. The county with the smallest proportion of notifications with at least one conviction was Stockholm with 18,2 %. In situations when the ownership of the animal was forbidden or when the animal keeper lacked different appropriate permissions (both included in “övriga”), the proportion of convictions was smallest at 32 %. No results were significant, but there were some interesting differences in the study. For example, there were differences between the counties in terms of both if the case went to prosecution or not, and if the case got a conviction or not. Especially, Stockholm was the one county administrative board who stood out with the lowest percentage of all solved cases. A small scattering was seen which cases occurred in all notifications of prosecution, where lack of veterinary care and inadequate supervision by the animal keeper were most common. The result in this study also showed that no correlation could be drawn between the deficiency case concerned and if the outcome was a conviction.